The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00436-018-6041-1
|View full text |Cite
|
Sign up to set email alerts
|

Population structures of Leishmania infantum and Leishmania tropica the causative agents of kala-azar in Southwest Iran

Abstract: Visceral leishmaniasis (VL) is endemic in Iran and is caused predominantly by Leishmania infantum, but L. tropica is emerging as an important cause. We studied the intra-species population structure of Leishmania spp. causing VL in southwest Iran by sequence analysis of the internal transcribed spacer (ITS) 1 of DNA samples from 29 bone marrow aspiration smears. L. infantum (n = 25) and L. tropica (n = 4) were identified, consisting of 10 and three ITS1 sequence types (STs), respectively. Compared to GenBank I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…In Iran, viscerotropic disease was first reported in 2006 in a patient from southwestern Iran, and more cases have since been reported from several regions in Iran (23,69). The frequencies of L. tropica-associated VL were 1.4% in 1993-1994 (69); 9% of bone marrow samples in patients were from southeast provinces (72) and 14% of patients were from southwest Iran (17).…”
Section: Tropica and Vlmentioning
confidence: 99%
See 2 more Smart Citations
“…In Iran, viscerotropic disease was first reported in 2006 in a patient from southwestern Iran, and more cases have since been reported from several regions in Iran (23,69). The frequencies of L. tropica-associated VL were 1.4% in 1993-1994 (69); 9% of bone marrow samples in patients were from southeast provinces (72) and 14% of patients were from southwest Iran (17).…”
Section: Tropica and Vlmentioning
confidence: 99%
“…There are genetic similarities between northwest Iranian L. infantum strains and hybrid strains of L. infantum/L. donovani in Cukurova in southeast Turkey (17). The recent arrival of refugees from Syria will add additional genetic heterogeneity to the L. tropica genetic pool in Turkey (86).…”
Section: Distribution Of CL and Related Causative Agents In The Neighmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the estimated incidence of the disease is 300–600 individuals (Alvar et al, ), new epidemiological changes have been reported in Iran. According to the increasing number of viscerotropic cases, L. tropica , the most important aetiological agent of anthroponotic CL (ACL), has been recently known as the second aetiological agent of VL in this country (Ghatee, Mirhendi, et al, ). Also, new emerging foci of ZVL have been found in western and north‐eastern parts of the country (Fakhar et al, ; Hamzavi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies in the province, it could be expected that L. major is the predominant species in the area. On the other hand, the traits of Tatera indica (reservoir) and Phlebotomus papatasi (vector) in the area, as well as various documentations from Khuzestan province, implicate this province along with Ilam and Bushehr provinces as the most highlighted regions for zoonotic cutaneous leishmaniasis in Iran (3,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%